Developmental dynamics and early growth vigour in rice. I. Relationship between development rate (1/phyllochron) and growth - Rebolledo, M.C.; Dingkuhn, M.; Péré, P.; McNally, K.L.; Luquet, D. (Wiley, 2012)
Achieving early vigour, that is, rapid dry matter accumulation, is a priority in rice crop improvement, but this trait is complex and not well understood genetically and physiologically. This study tested the hypothesis that the development rate (DR) contributes to early vigour. Two diversity panels were phenotyped during vegetative stage for traits constituting early vigour (shoot dry weight, SDW; relative growth rate, RGR) or contributing to early vigour (tillering, leaf size, DR). The first panel comprised 169 genotypes from all major genetic groups of Oryza sativa and was phenotyped under irrigated upland conditions in the field (Philippines, Exp1). The second panel with 190 genotypes representing the diversity of the tropical japonica group was phenotyped in pots in a greenhouse (Montpellier, France, Exp2). Results from field and pot experiment pointed out that DR, tillering and leaf size were positively correlated with RGR and SDW, although the contribution of leaf size was small. DR was positively correlated with tillering but both were negatively correlated with leaf size. DR vs. RGR correlation was conserved in subsets of genotypes with similar leaf size and tillering, suggesting an effect of DR on RGR independent of the other traits. DR is a promising, still underexploited trait contributing to rice early vigour, requiring further genetic and physiological characterization.